2015
DOI: 10.1016/j.berh.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Pain in systemic connective tissue diseases

Abstract: Pain is frequent in patients with connective tissue diseases (CTDs), particularly those affected by systemic sclerosis (SSc) and systemic lupus erythematosus (SLE) in which it is virtually ubiquitous and can have different causes. The SLE classification criteria include pain associated with musculoskeletal involvement, which are frequently the initial symptom of SLE and can include arthralgia, arthritis and/or myalgia. Chronic widespread pain, the cornerstone of fibromyalgia (FM), is also frequently associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…In this study, persistent users disproportionately utilized the ED compared to limited users, and mostly for non‐lupus–related pain reasons. Chronic pain, a symptom frequently experienced by patients with SLE , was a major cause of ED utilization and ED‐initiated admissions among patients with SLE who persistently frequented the ED. These patients were more likely to be noncritically ill, as evidenced by frequent discharge from the ED and PASS admissions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, persistent users disproportionately utilized the ED compared to limited users, and mostly for non‐lupus–related pain reasons. Chronic pain, a symptom frequently experienced by patients with SLE , was a major cause of ED utilization and ED‐initiated admissions among patients with SLE who persistently frequented the ED. These patients were more likely to be noncritically ill, as evidenced by frequent discharge from the ED and PASS admissions.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] SLE can also be a painful disease, with pain ranging from musculoskeletal (affecting bone, muscles, joints) to centralised (related to fibromyalgia and the central nervous system) systems. [5][6][7][8] There is currently no cure for SLE, standard of care has relied on a combination of antimalarials, corticosteroids and/or immunosuppressants depending on disease severity. 9 Biological therapy was introduced for SLE almost a decade ago with belimumab, a B-lymphocyte stimulator cell-targeting therapy; however, treatment pattern studies have shown a relatively low uptake of this biologic in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…However, effective pain management has not been investigated in detail in patients with SSc and the experience in DUs is further limited, particularly regarding opioids such as oxycodone. 11 , 12 Due to the lack of best practice consensus, analgesic strategies are not standardized and are mainly guided by a physician’s experience.…”
Section: Introductionmentioning
confidence: 99%